Trade Policy Uncertainty and Exports: Evidence from China's WTO Accession - Ling Feng; Zhiyuan Li; Deborah L. Swenson (Center for Economic Studies and ifo Institute (CESifo), 2014)
To understand the effects of trade policy uncertainty on firm-level export decisions, we study firm-product data on Chinese exports to the U.S. in the years surrounding China's 2001 WTO accession. Following predictions based on a model of heterogeneous firms, we provide empirical evidence that product-level tariff uncertainty reduction spurred a notable reallocation of export activities across firms, largely due to extensive margin entries and exits. In addition we document accompanying changes in prices and quality that coincided with this reallocation: firms that provided higher quality products at lower prices entered the U.S. export market, while firms that had higher prices and provided lower quality products exited.
Keywords: F13; F14; D81; F51; 330